Analisis motivasi belajar dalam menguraikan informasi paparan iklan pada pembelajaran bahasa indonesia kelas V sekolah dasar - Novita Dwi Puspitaningrum; Retno Winarni; Joko Daryanto (Didaktika Dwija Indria, 2022)
The purpose of this study was to describe the learning motivation of fifth grade elementary school students in describing advertising exposure information. This study used qualitative research methods. The subjects of this study were seven fifth grade students at SDN Mangkubumen Lor No. 15 Surakarta for the 2021/2022 academic year. This study uses data collection techniques in the form of interviews, observation, and documentation studies. The data analysis used is an interactive analysis model consisting of data collection, data reduction, data presentation, and conclusion/verification. The results showed that students with low learning motivation had a percentage of 28.57%. Students with sufficient learning motivation have a percentage of 28.57%. Students with high learning motivation have a percentage of 28.57%. While students with very high learning motivation have a percentage of 14.29%. There are seven indicators of learning motivation to determine the level of student learning motivation, including: being diligent in facing assignments and completing them, facing difficulties tenaciously and never giving up, showing interest in dealing with problems, independent learning, getting bored quickly. on assignment. - Routinely do assignments, defend and convince opinions with good and strong reasons, and like to find problems and solve problems.